أثر تفاعل كل من اليقظة العقلية والتراحم بالذات والحساسية الانفعالية في التنبؤ بقلق المستقبل المهني لدى الطلاب المعلمين: دراسة سيكومترية - كلينيكية - محمد، محمد شعبان أحمد; عبدالجواد، أحمد سيد عبدالفتاح (جامعة الفيوم - كلية التربية, 2022)
هدفت هذه الدراسة إلى التعرف على أثر تفاعل كل من اليقظة العقلية والتراحم بالذات والحساسية الانفعالية في التنبؤ بقلق المستقبل المهني لدى الطلاب المعلمين. واعتمدت الدراسة على استخدام المنهج الوصفي والمنهج الكلينيكي. وقد أجريت الدراسة على عينة قوامها (475) طالبا وطالبة بالفرقتين الثالثة والرابعة بكليات التربية (تعليم عام وأساسي) والتربية النوعية والتربية للطفولة المبكرة بجامعة الفيوم. وقام الباحثان بإعداد أدوات الدراسة المتمثلة في: مقياس اليقظة العقلية، ومقياس التراحم بالذات، ومقياس الحساسية الانفعالية، ومقياس قلق المستقبل المهني، بالإضافة إلى استخدام اختبار تفهم الموضوع (TAT). وتوصلت الدراسة إلى مجموعة من النتائج أهمها: وجود علاقة ارتباطية سالبة دالة إحصائيا بين اليقظة العقلية وقلق المستقبل المهني، ووجود علاقة ارتباطية سالبة دالة إحصائيا بين التراحم بالذات وقلق المستقبل المهني، ووجود علاقة ارتباطية موجبة دالة إحصائيا بين الحساسية الانفعالية وقلق المستقبل المهني. وقد ظهرت فروق دالة إحصائيا في اليقظة العقلية تعزى لمتغير النوع لصالح الذكور، في حين لم تظهر فروق دالة إحصائيا في التراحم بالذات تعزى لمتغير النوع، وكذلك ظهرت فروق دالة إحصائيا في الحساسية الانفعالية تعزى لمتغير النوع لصالح الإناث، وظهرت فروق دالة إحصائيا في قلق المستقبل المهني تعزى لمتغير النوع لصالح الإناث. وظهرت كذلك فروق دالة إحصائيا بين مرتفعي ومنخفضي قلق المستقبل المهني من عينة الدراسة في كل من اليقظة العقلية والتراحم بالذات والحساسية الانفعالية. وقد ظهر تأثير دال لتفاعل كل من اليقظة العقلية والتراحم بالذات والحساسية الانفعالية على قلق المستقبل المهني لدى عينة الدراسة. كما أن متغيرات اليقظة العقلية والتراحم بالذات والحساسية الانفعالية تسهم في التنبؤ بقلق المستقبل المهني لدى عينة الدراسة. وأظهرت نتائج تطبيق اختبار تفهم الموضوع TAT اختلاف الصور الكلينيكية للحالة مرتفعة قلق المستقبل المهني عنها للحالة منخفضة قلق المستقبل المهني. This study aimed to identify the impact of the interaction of mental alertness, self-compassion, and emotional sensitivity in predicting future professional anxiety among student teachers. The study relied on the use of the descriptive approach and the clinical approach. The study was conducted on a sample of (475) male and female students in the third and fourth grades in the faculties of education (general and basic education), specific education and early childhood education at Fayoum University. The researchers prepared the study tools, which are: the mental alertness scale, the self-compassion scale, the emotional sensitivity scale, and the professional future anxiety scale, in addition to using the subject understanding test (TAT). The study found a set of results, the most important of which are: there is a statistically significant negative correlation between mental alertness and professional future anxiety, and there is a statistically significant negative correlation between self-compassion and professional future anxiety, and there is a positive, statistically significant correlation between emotional sensitivity and professional future anxiety. There were statistically significant differences in mental alertness due to the gender variable in favor of males, while there were no statistically significant differences in compassion in particular due to the gender variable, as well as statistically significant differences in emotional sensitivity due to the gender variable in favor of females, and there were statistically significant differences in professional future anxiety. It is attributed to the gender variable in favor of females. There were also statistically significant differences between high and low professional future anxiety of the study sample in both mental alertness, self-compassion and emotional sensitivity. There was a significant effect of the interaction of mental alertness, self-compassion, and emotional sensitivity on the professional future anxiety of the study sample. The variables of mental alertness, self-compassion, and emotional sensitivity contribute to predicting future professional anxiety among the study sample. The results of applying the subject understanding test showed that the clinical picture of the case with high professional future anxiety differed from that of the case with low professional future anxiety.
Keywords: اليقظة العقلية -- الحساسية الانفعالية -- القلق المهني -- طلبة كلية التربية -- مصر